2018
DOI: 10.1101/345033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transfer Learning for Task Adaptation of Brain Lesion Assessment and Prediction of Brain Abnormalities Progression/Regression using Irregularity Age Map in Brain MRI

Abstract: The Irregularity Age Map (IAM) for the unsupervised assessment of brain white matter hyperintensities (WMH) opens several opportunities in machine learning-based brain MRI analysis, including transfer task adaptation learning in the MRI brain lesion's segmentation and prediction of lesion progression and regression. The lack of need for manual labels is useful for transfer learning. Whereas, the nature of IAM itself can be exploited for predicting lesion progression/regression. In this study, we propose the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We believe that the irregularity map could provide unsupervised information for pre-training supervised deep learning, such as UResNet and UNet. In (Rachmadi et al, 2018a), UNet successfully learned the irregularity map produced by LOTS-IM. Progression/regression of brain abnormalities also can be achieved with LOTS-IM (Rachmadi et al, 2018a).…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that the irregularity map could provide unsupervised information for pre-training supervised deep learning, such as UResNet and UNet. In (Rachmadi et al, 2018a), UNet successfully learned the irregularity map produced by LOTS-IM. Progression/regression of brain abnormalities also can be achieved with LOTS-IM (Rachmadi et al, 2018a).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In (Rachmadi et al, 2018a), UNet successfully learned the irregularity map produced by LOTS-IM. Progression/regression of brain abnormalities also can be achieved with LOTS-IM (Rachmadi et al, 2018a). Due to its principle, it could be applicable to segment brain lesions in CT scans or different brain pathologies, but further evaluation would be necessary.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…IM is also independent from a human rater or training data, as it is produced using an unsupervised method (i.e., LOTS-IM) (Rachmadi et al, 2019b). Furthermore, previous studies have shown that IM can also be used for WMH segmentation (Rachmadi et al, 2018b), data augmentation of supervised WMH segmentation (Jeong et al, 2019), and simulation of WMH progression and regression (Rachmadi et al, 2018c). DEM resulted from the subtraction of two IMs has values ranging from -1 to 1 (first row of Figure 1).…”
Section: Disease Evolution Map (Dem)mentioning
confidence: 99%